Interview with Francesco Careri - Arredondo Garrido, David (SOBRE, 2018)
Francesco Careri is a professor of Urban Planning at the Dipartimento di Architettura of the Università degli Studi Roma Tre. His book Walkscapes, published by Gustavo Gili in 2002, provided a brand-new look at landscape, laying the foundations for the understanding of walking as an aesthetic practice. With references such as Land Art and Situationism, Careri and the Stalker group (to which he has belonged to since the mid- 1990s), have published their work widely, given conferences and, most importantly, gone on walks throughout the world to recognize territories from new perspectives. To wander across lesser known landscapes, to climb walls, to cross wire fences, to trip or to get injured… become tools to experience, through one’s own body, an urban reality which cannot be grasped by means of books and theories. Through his Laboratory of Civic Arts, he proposes, along with his students, this free and unprejudiced way of reading and understanding the cities; where there is still much to be said. In this interview, conducted in February 2017, we delve into some of these issues related to Stalker, and his work as a professor and as a writer.